Prevalence of Upper Extremity Function following Transradial Percutaneous Coronary Intervention - Rahman Ullah, Muhammad Haroon Abdullah, Aan-E-Arshad Sh, Zeeshan Shoukat, Sharafat Hussain, Hajra Tariq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: The most frequently used technique for percutaneous coronary intervention (PCI) is the transradial approach (TRA). The purpose of the present study was to determine the prevalence of upper extremity function following transradial percutaneous coronary intervention. Patients and Methods: This cross-sectional study was conducted on 280 patients hospitalized for percutaneous coronary intervention in the Cardiology Department of MTI Lady Reading hospital, Peshawar and Lahore General Hospital from March 2022 to December 2022. Patients with palpable radial artery and non-occlusive flow confirmed by Doppler ultrasound examination were enrolled. Patients were divided into two groups: Group-I (underwent transradial approach (TRA)) and Group-II (treated with transfemoral PCI (TF-PCI). All the clinical outcomes were measured after 6 months follow-up. SPSS version 27 was used for data analysis. Results: Of the total 280 patients, the Group-I and Group-II had 220 and 60 patients respectively. During follow-up, the Group-I patients had higher incidence of upper extremity dysfunction (UED) (34.8%) than control or group-II patients (12.8%). Wrist extension, flexion, and elbow extension was the prime reasons for the upper extremity dysfunction. Smokers were three time at higher risk of developing upper extremity dysfunction. Conclusion: It has been observed that UED appears to occur twice as frequently in group-I as in group-II. Reduced rate of site complication and enhanced patient’s satisfaction has been found in group-I as compared to group-II. Keywords: Upper extremity function, percutaneous coronary intervention, transradial approach